(untitled) (Economic studies journal, 2020)
This study is intended to identify a commitment of Libyan commercial banks with the characteristic of forming audit committees. To achieve the objective of the study, it was designed a survey distributed to the area of the study component of Libyan commercial banks located between the cities of Ras Lanuf and Hisha Al-Jadeeda where a number of questionnaires were handed out to 13 banks. A total of 49 questionnaires were distributed to bank managers and their assistants, internal audit department heads and staff, heads and staff of current account sections and some other staff, of which 38 questionnaires were returned and valid for analysis. The Social Science Statistical Package Program has been used (SPSS) to process the collected data. This is done using descriptive statistics and indicative statistics for data analysis. The study reached several results, the most important of which are Libyan commercial banks adhere to the characteristics of forming audit committees, this was made clear by their commitment to all of the independence characteristic, the characteristic of scientific qualification, financial and accounting experience, the size of audit committee. In addition, the study found that there was no difference between the views of the sample study on the extent of commitment of Libyan commercial banks to the characteristics of forming audit committees. Based on the findings of the study, the study recommends that the capabilities of the board members of Libyan commercial banks should be strengthened this is done by conducting ongoing training courses for them on how to set up the review committees, in line with the updates and the latest developments in this field.